2017
DOI: 10.1177/0972150917713274
|View full text |Cite
|
Sign up to set email alerts
|

Outsource Services to Improve Financial Performance: Is There a Limit?

Abstract: Outsourcing has been identified as one of the key factors for improving companies’ financial performance. Moreover, the procurement of business services has become an important element of companies’ acquisition of external resources. However, there is a lack of evidence linking services outsourcing and performance. Limited prior literature has mostly assumed that this relationship is positive and linear. Our empirical study reveals that firms may be able to increase their performance through services outsourci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, flexibility in processes, mass customization and serving end users with high varieties have become comparatively simple by making better use of available logistics services. Organizations usually outsource their forward and reverse logistics activities to logistics service providers (LSPs) with the purpose of focusing more on their core competency, reduction in costs, improvements in deliverables, scaling business to a wider network reach and improving their supply chain (Sanchís-Pedregosa, Gonzalez-Zamora & Palacín-Sánchez, 2017). Logistics providers or third party logistics (3PLs) have marked their importance by delivering many direct and indirect benefits to the end users by managing smooth flow of materials across up/down stream of supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, flexibility in processes, mass customization and serving end users with high varieties have become comparatively simple by making better use of available logistics services. Organizations usually outsource their forward and reverse logistics activities to logistics service providers (LSPs) with the purpose of focusing more on their core competency, reduction in costs, improvements in deliverables, scaling business to a wider network reach and improving their supply chain (Sanchís-Pedregosa, Gonzalez-Zamora & Palacín-Sánchez, 2017). Logistics providers or third party logistics (3PLs) have marked their importance by delivering many direct and indirect benefits to the end users by managing smooth flow of materials across up/down stream of supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Studies across different industries and types of outsourced services have shown that the outcomes of outsourcing events frequently fall short of managers' hopes, and that outsourcing can introduce new frustrations. Even if cost savings materialize from an outsourcing event, they 6 may not be as significant as anticipated, and they may not be sufficient to justify the transition (Caldwell, 1997;Greenberg & Canzoneri, 1997;Fan, 2000;Kang et al, 2012;Sanchís-Pedregosa et al, 2017).) Critiques of outsourcing in the public sector have been especially pronounced.…”
Section: Questions and Critiquesmentioning
confidence: 99%